Kajian Ilmu Filsafat dalam Identifikasi Iman serta Relevansinya dalam Kehidupan Orang Kristen - Warae, Olohesi; Ndraha, Pris Kristiani; Lawalata, Mozes (Sekolah Tinggi Teologi Berita Hidup, 2024)
In this article discuss about the complexity of the definition of faith in the context of theology and philosophy and the need to understand the rational basis for religious belief. His research problem involves the question of how philosophy can help christians understand, explain and strengthen their faith. In this study, central concepts of the christian faith such as faith in God, the exsistence of evil in the world and human freedom are analized analyticallly using a philosophical approach. The main results of this research indecate that phylosophy provides a rational framework for understanding fait and provides tools for Christians to reflect on and strengthen their faith. Through philosophical analysis, christians can explore the theological implications of their beliefs more deeply and understand the relationship between faith and rational thought. Additionally, this research emphasizes that the use of philosophical knowledge in the context of Christianity helps strengthen the intellectual foundations of this faith, which in turn can strengthen the resilience of the faith and clarify difficult questions of this world. Christians know that God is the source of truth. All truths formulated by philosophy are never higher than God's truth, namely the truth of the Bible which is the valid source. This. as Christians, we must need criteria to be able to test truth, views and understanding, in the midst study confirms that philosophy plays an important role in identifying the christian faith and the daily lives of christians. By profiding an analytical framework, philosophy helps deepen understanding of faith